Experimental and fragility analysis of threaded cast iron pipe fittings utilized in a fire suppression system - Rusnak, Cameron R.; Elfass, Sherif A.; Rivas, Allen J. (Frontiers in Built Environment, 2025)
Fire suppression piping systems utilize threaded connections to join pipes with fittings, such as elbows and tees, enabling the distribution of water throughout a structure. These fittings are essential for directional changes and navigating complex building designs. However, while prior research has examined the mechanical behavior of threaded connections at the pipe-fittings interface, limited attention has been given to the structural performance of the threaded fittings themselves. This study addresses this gap by investigating the mechanical behavior, rotational capacity, and failure modes of threaded cast iron fittings under quasistatic loading. Experimental testing was conducted at the University of Nevada, Reno, involving twenty-seven tests on elbows and tees with diameters of 1-inch, 1.5-inches, and 2-inches. The fittings were subjected to quasi-static loading to evaluate their structural response, particularly their rotational capacity and failure mechanisms. Results indicate that leakage at the pipe-fitting interface is the primary failure mode, despite significant rotation occurring within the fitting body. The average rotational capacity was approximately 28 kip-ft per radian within the fitting and 8 kip-ft per radian at the pipe/fitting interface. Additionally, larger diameter fittings demonstrated significantly reduced deformation compared to smaller fittings, with an average reduction of approximately 63% in capacity relative to the next smallest size. Based on these findings, damage states were defined, rotational capacities established, and seismic fragility models were developed for each fitting size. These results provide critical insights into the structural performance of threaded cast iron fittings, contributing to improved design guidelines and safety assessments for fire suppression piping systems.